Determination of Leuprolide in Beagle Dogs' Serum by High Performance Liquid Chromatography-Mass Spectrometry and Study on Bioequivalence - Xiong, D.M.; Wen, S.L.; Chen, H.; Bao, X.; Ye, L.M. (Asian Journal of Chemistry, 2014)
An HPLC-MS/MS method was used to calculate the pharmacokinetic parameters and to evaluate the bioequivalence versus equal dose of test or reference leuprolide microspheres in male healthy beagle dogs. The MS-MS detection was made by monitoring 605.5®221.3 (m/z) for leuprolide and 584.4®221.3 (m/z) for the I.S. The dynamic range was from 0.103-103 ng mL-1. The recovery rate was 78.75-90.77 % and matrix effect was -5.25-10.3 %. The intra- and inter-assay precisions were with relative standard deviations (RSDs) of £ 5.19 % (n = 6) and £ 6.48 % (n = 6), respectively. Evaluation of bioequivalence was made by analysis of variance, Double-sided t-test and (1-2a) confidence interval method. The results show the test agents, the AUC0®t leuprolide 90 % confidence interval for the reference preparation of the corresponding parameters of 99.6-102.5 %, the AUC0®¥ leuprolide 90 % confidence interval for the reference preparation of the corresponding parameters of 90.2-103.9 %, Cmax 90 % confidence interval for the reference preparation of the corresponding parameters of 91.0-129.8 %.